Spina Bifida Occulta with Bilateral Spondylolysis at the Thoracolumbar Junction Presenting Cauda Equina Syndrome - Kentaro Mataki; Masao Koda; Yosuke Shibao; Hiroshi Kumagai; Katsuya Nagashima; Kousei Miura; Hiroshi Noguchi; Toru Funayama; Tetsuya Abe; Masashi Yamazaki (Case Reports in Orthopedics)
Several reports have described the coexistence of spina bifida occulta (SBO) and spondylolysis, but the majority of defects occur at L5. No report has described the coexistence of SBO and spondylolysis at the thoracolumbar junction. We report a case of SBO with spondylolysis at L1, presenting cauda equine syndrome. A 37-year-old man presented with a gait disorder as a result of bilateral motor weakness of the lower extremities. A plain radiograph showed local kyphosis at L1-2 as a result of severe degenerative change and wedging of the vertebral body at L1. Magnetic resonance imaging (MRI) revealed degenerative disc changes and severe canal stenosis at L1-2. Computed tomography (CT) revealed SBO and spondylolysis at L1. He was diagnosed with cauda equina syndrome related to SBO and spondylolysis at L1. Posterior interbody fusion and decompression at L1-2 were performed. After surgery, his muscle power recovered to normal strength. The possible mechanisms in this case are the strain on anterior elements as a result of disruption of the posterior elements due to SBO and spondylolysis. The coexistence of SBO and spondylolysis at the thoracolumbar junction might induce at-risk status of increased strain to the anterior elements that may cause cauda equina syndrome.